2017
DOI: 10.1515/demo-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Kendall’s tau and agglomerative clustering for structure determination of hierarchical Archimedean copulas

Abstract: Several successful approaches to structure determination of hierarchical Archimedean copulas (HACs) proposed in the literature rely on agglomerative clustering and Kendall's correlation coe cient. However, there has not been presented any theoretical proof justifying such approaches. This work lls this gap and introduces a theorem showing that, given the matrix of the pairwise Kendall correlation coe cients corresponding to a HAC, its structure can be recovered by an agglomerative clustering technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As the structure estimator in Górecki et al (2016Górecki et al ( , 2017c does not, by contrast to Okhrin et al (2013a), require any assumptions on the family of the nested ACs, it is thus immediately feasible also for HOPAC estimation. Moreover, there exist theoretical justifications for such an estimator -given a HAC, Okhrin, Okhrin and Schmid (2013b) show that its structure can be uniquely recovered from all its bivariate margins, and Theorem 2 in Górecki, Hofert and Holeňa (2017b) show that it is possible just from all its pairwise Kendall's coefficients. Finally, as this estimator, formalized by Algorithm 1 in Górecki et al (2017c) (see also our Appendix), showed the best results in the ratio of successfully estimated true HAC structures on the basis of simulation studies, see Górecki et al (2016) or Uyttendaele (2017), we adopt it to our HOPAC estimation approach.…”
Section: Estimating Hopacsmentioning
confidence: 99%
“…As the structure estimator in Górecki et al (2016Górecki et al ( , 2017c does not, by contrast to Okhrin et al (2013a), require any assumptions on the family of the nested ACs, it is thus immediately feasible also for HOPAC estimation. Moreover, there exist theoretical justifications for such an estimator -given a HAC, Okhrin, Okhrin and Schmid (2013b) show that its structure can be uniquely recovered from all its bivariate margins, and Theorem 2 in Górecki, Hofert and Holeňa (2017b) show that it is possible just from all its pairwise Kendall's coefficients. Finally, as this estimator, formalized by Algorithm 1 in Górecki et al (2017c) (see also our Appendix), showed the best results in the ratio of successfully estimated true HAC structures on the basis of simulation studies, see Górecki et al (2016) or Uyttendaele (2017), we adopt it to our HOPAC estimation approach.…”
Section: Estimating Hopacsmentioning
confidence: 99%
“…This algorithm can be used for arbitrary d > 2 (see Górecki and Holeňa (2013) for more details including an example for d = 4). It returns the sets U C (ψ k ), k = 1, ..., d − 1.…”
Section: Our Approachmentioning
confidence: 99%
“…The literature on structure learning for these models is emerging. For example, algorithms have begun to be developed for hierarchical Archimedean copulas, see, e.g., Okhrin et al (2013); Segers and Uyttendaele (2014); Górecki et al (2016Górecki et al ( , 2017; Cossette et al (2019) and references therein. Learning the block structure of a matrix of pair-wise Kendall's tau under the partial exchangeability of the copula has been considered by Perreault et al (2019).…”
Section: Introductionmentioning
confidence: 99%